Experiencing the lifespan - Belsky, Janet, 1947- (New York Worth publisher, 2019)
Janet Belsky's text offers a fresh, remarkably brief way to understand the experience of human development throughout the lifespan. It gives students an immediate and practical grounding in the field's basic concepts, guiding them from underlying research to practical applications, in a highly conversational style, with pedagogy that reinforces learning, and with examples drawn from an extraordinarily broad range of cultures throughout the world. Exceptionally well-loved by instructors and students who've used it.
Part I The foundation: The people and the field -- Prenatal development, pregnancy, and birth // Part II Infancy and toddlerhood: Physical and cognitive development in infants and toddlers -- Emotional and social development in infants and toddlers // Part III Childhood: Early childhood -- Middle childhood -- Settings for development: home, school, and community // Part IV Adolescence: Physical development in adolescents -- Cognitive, emotional, and social development in adolescents // Part V Early and middle adulthood: Constructing an adult life -- Social development: relationships and roles -- Midlife // Part VI Later life: Later life: cognitive, emotional, and social development -- The physical challenges of old age // Part VII Endings: Death and dying.
Includes bibliographical references and indexes.
Keywords: Developmental psychology; Life cycle, Human; Life cycle, Human